Psychometric Properties of the Stress Coping Strategies Scale for Adolescents - Al-Hazzazi, Muhammad Yahya; Al-Ghamdi, Saleh Yahya (Journal of Educational and Psychological Sciences, 2025)
This study aimed to examine the psychometric properties of the Stress Coping Strategies Scale for a sample of adolescents in the Makkah region. The study was designed to develop a comprehensive scale that measures the coping strategies adolescents use to handle psychological stress, facilitating the understanding, interpretation, and analysis of their behaviors, and ultimately enabling appropriate intervention and counseling. The study adopted a descriptive-analytical methodology, focusing on describing and analyzing the psychometric characteristics of the Stress Coping Strategies Scale among adolescents. A purposive sample of 264 high school students (mean age = 17.27 years), representing middle adolescence, was selected from the Makkah region. A custom-designed scale was used, consisting of 14 dimensions and 30 items, covering various aspects of stress coping strategies. Statistical analysis was conducted using Exploratory Factor Analysis (EFA) to extract the scale’s dimensions. The results identified 14 factors, accounting for 76.454% of the total variance, indicating a strong relationship between the scale’s items and the identified dimensions. The Cronbach’s Alpha coefficient for the overall scale was 0.705, demonstrating its validity, reliability, and suitability for measuring stress coping strategies among adolescents with high accuracy. Based on the study findings, the researcher recommends developing specialized counseling programs to enhance stress coping strategies, as acquiring such strategies empowers adolescents to navigate stressful events and challenges more effectively and adapt more successfully.